AN ANALYSIS OF EFL STUDENTS’ TRANSITIVITY PROCESS OF WRITING RECOUNT TEXT - Yanti Rosmayanti (Universitas Galuh, 2021)
This paper focuses on the analysis of transitivity process contained in EFL students‟ writing recount text and dominant type of transitivity process in EFL students‟ writing recount text. Descriptive qualitative method is used to analyze the Transitivity Process of EFL students‟ writing recount text consisting of collecting data, classifying data, analyzing, and interpreting data. The document of this study is six EFL students‟ writing recount texts and there are 173 data consisting of clauses taken from the text. The finding reveals that there are six types of transitivity process contained in EFL students‟ recount text: material process, mental process, relational process, behavioral process, existential process and verbal process. Material process becomes the first mostly applied with the total number of occurrence 108 (62.43%) from overall data. Mental process becomes the second mostly applied with the total number of occurrence 26 (15.03%) from overall data. Relational process becomes the third mostly applied with the total number of occurrence 21 (12.14%) from overall data. Existential process is applied with the total number of occurrence 12 (6.94%) from overall data. Verbal Process is applied with the total number of occurrence 5 (2.88%) from all data; and the last, behavioral process is applied with the total number of occurrence 1 (0.58%) from overall data. Material Process is the dominant transitivity process types in all the EFL students‟ recount text with the total number of occurrence 108. Based on the findings, it is recommended that, Transitivity process should be applied in the educational field, for example, in the learning writing process, to help students in improving their achievement and their knowledge of in transitivity process. Keywords: Recount text, Transitivity process